Using Pre-Operative Incentive Spirometer Reduces Chances of Basal Atelectasis in Patients Undergoing Upper Abdominal Surgeries - A Randomized Controlled Trial - Naeem, Muhammad; Aziz, Majid; Saeed, Bilal; Hashmi, Syed Daood; Ali, Muhammad; Jalil, Meezan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare frequency of basal atelectasis in patients undergoing upper abdominal surgery who are provided pre-operative incentive spirometry versus those not provided pre-operative incentive spirometry. Study Design: Randomized controlled trial (NCT06115941). Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2023. Methodology: We included 74 patients who were scheduled for upper abdominal surgery and divided them into group-A “Pre-op spirometry group” and group-B “no pre-op spirometry group”. Patients who underwent lower abdominal surgery were excluded. Patients were assessed at 48 hours after surgery for presence of basal atelectasis. Data was analyzed by statistical package for social sciences 22. Results: In our study, mean age of the patients was 37.97±5.36 years. 51(68.92%) male and 23(31.08%) female subjects were included. No significant difference between groups was observed in terms of mean age, gender distribution, mean BMI and median duration of ventilator support (p>0.05). Frequency of basal atelectasis in “incentive spirometry “group-A was 3(8.11%) while in “no incentive spirometry” group-B it was 11(29.73%), (p=0.018). Conclusion: Although Incentive Spirometry is utilized for management of basal atelectasis but it is also highly useful in reducing frequency of post-op basal atelectasis when used pre-operatively.